Dinâmicas territoriais do espaço agrário na Amazônia: a dendeicultura na microrregião de Tomé-Açu (PA) - João Santos Nahum; Antonio Tiago Corrêa Malcher (Confins)
We examine some aspects of territorial dynamics driven by the culture of palm oil in the Amazon in Pará, specifically in the micro region of Tome-Açu. We analyzed this space how the uses are designed from the territory controlled by private interests of palm culture; uses that threaten their production of the peasant way of life, especially with the formation of the land market and also the association between of palm oil agribusiness and family farming. We reflect on these impacts, without the concern of exhausting them. We raise secondary data from literature review and consultation at websites. The information and primary data were collected and systematized by fieldwork, where we were able to put the land of the place under the nails and so describe the processes surveyed. In the first part outlined in broad lines the periodization of palm culture in the micro region of Tomé-Açu, the objective is to highlight the expansion of this culture. In the second part we analyze the impacts of this process on the peasantry, especially through the formation of the land market and association with oil palm farmers groups.